Inefficacy of Immunosuppressive Therapy for Severe Aplastic Anemia Progressing From Non-SAA: Improved Outcome After Allogeneic Hematopoietic Stem Cell Transplantation - Liu, Limin; Zhao, Xin; Miao, Miao; Zhang, Yanming; Jiao, Wenjing; Lei, Meiqing; Zhou, Huifen; Wang, Qingyuan; Cai, Yifeng; Zhao, Liyun; Shangguan, Xiaohui; Liu, Zefa; et al. (Frontiers in Oncology, 2021)
Background and Aims This study aimed at comparing the efficacy and safety of severe aplastic anemia (SAA) cases that had met the criteria for SAA at the time of diagnosis (group A) with SAA that had progressed from non-SAA (NSAA) (group B), both undergoing first-line immunosuppressive therapy (IST). Additionally, group B was compared with SAA that had progressed from NSAA and who had been treated by allogeneic hematopoietic stem cell transplantation (allo-HSCT) (group C). Methods We retrospectively compared 608 consecutive patients in group A (n = 232), group B (n = 229) and group C (n = 147) between June 2002 and December 2019. Six months after treatment, the rate of overall response and the fraction of patients who had achieved normal blood values, treatment-related mortality (TRM), secondary clonal disease, 5-year overall survival (OS) and failure-free survival (FFS) were indirectly compared between group A and group B, group B and group C. Results Six months after treatment, the rate of overall response and the fraction of patients who had achieved normal blood values in group A was higher than in group B (65.24% vs. 40.54%, P < 0.0001; 23.33% vs. 2.25%, P < 0.0001); the same was true for group C (92.50% vs. 2.25%, P < 0.0001). The rate of relapse in group B was higher than in group C (P < 0.0001), but there were no differences in TRM and secondary clonal disease (P > 0.05). There were no differences in estimated 5-year OS between groups A and B (83.8% ± 2.6% vs. 85.8% ± 2.6%, P = 0.837), or between B and C (85.8% ± 2.6% vs. 77.9% ± 3.4%, P = 0.051). The estimated 5-year FFS in groups A and C was higher than for group B (57.1% ± 3.3% vs. 39.7% ± 3.4%, P < 0.001; 76.7% ± 3.5% vs. 39.7% ± 3.4%, P < 0.0001). Conclusion These results indicate that IST is less effective in SAA progressing from non-SAA but allo-HSCT can improve outcomes.